Effect of four selected plant powder as rice grain protectant against sitophilus zeamais(Coleoptera: Curculionidae) - Asmanizar; Djamin, A; Idris, A.B (Universiti Kebangsaan Malaysia, 2012)
A study to evaluate the effect of four selected plant powder as rice grain protectant against Sitophilus zeamais adult mortality, F1 progeny production, weight loss and rice grain damaged was conducted. The plant powders used were made from seed of Annona muricata, Jatropha curcas, Azadirachta indica and from leaf of J. curcas at 0.5, 1, 1.5, 2 and 2.5% (w/w) concentrations. Probit analysis showed that J. curcas seed powder was highly toxic (LC50 = 0.28%) to S. zeamais adult followed by A. muricata seed (LC50 = 0.33%), J. curcas leaf (LC50 = 1.15%) and A. indica seed (LC50 = 3.63%). The Annona muricata and J. curcas seed had caused the highest mean mortality (100 and 98.85%) at 2% concentration, while the A. indica seed and J. curcas leaf powder had only caused 32.32 and 77.84%, respectively at 2.5% concentration. There was no progeny produced, no weight loss recorded and no rice grain damaged on treated rice grain with A. muricata and J. curcas seed at 1% concentration. In contrast, J. curcas leaf and A. indica seed powder had the least toxicity effect on the weevil as shown by number of progeny produced (167 and 228), total of weight loss (10.04 and 10.49%) and rice grain damaged (19.35 and 21.14%) even at the highest powder concentration (2.5%) tested. Results of this study revealed the potential of J. curcas and A. muricata seed powder to be used in controlling S. zeamais on stored rice grain.